2020
DOI: 10.3389/fgene.2020.00067
|View full text |Cite
|
Sign up to set email alerts
|

NanoGBS: A Miniaturized Procedure for GBS Library Preparation

Abstract: High-throughput reduced-representation sequencing (RRS)-based genotyping methods, such as genotyping-by-sequencing (GBS), have provided attractive genotyping solutions in numerous species. Here, we present NanoGBS, a miniaturized and eco-friendly method for GBS library construction. Using acoustic droplet ejection (ADE) technology, NanoGBS libraries were constructed in tenfold smaller volumes compared to standard methods (StdGBS) and leading to a reduced use of plastics of up to 90%. A high-quality DNA library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…GBS was conducted following the methods and recommendations outlined by Elshire et al (2011) , Sonah et al (2013) , and Torkamaneh et al (2020a , c) . The GBS library was created with Ape KI restriction enzyme digestion.…”
Section: Methodsmentioning
confidence: 99%
“…GBS was conducted following the methods and recommendations outlined by Elshire et al (2011) , Sonah et al (2013) , and Torkamaneh et al (2020a , c) . The GBS library was created with Ape KI restriction enzyme digestion.…”
Section: Methodsmentioning
confidence: 99%
“…To validate these simulations experimentally, we constructed GBS libraries for a set of 96 diverse soybean accessions using Bfa I digestion and the standard GBS (Std‐GBS) protocol (Torkamaneh et al ., 2020a). After size selection and PCR amplification, the quality of the GBS library was assessed and the resulting profile (Figure 1b) indicated that the vast majority of size‐selected fragments (including sequencing adapters) ranged between 200 and 600 bp.…”
Section: Figurementioning
confidence: 99%
“…Genotyping cost per sample can be dramatically decreased by miniaturizing library preparation (e.g. NanoGBS) and an increased multiplexing level (Torkamaneh et al ., 2020a). We also developed a plate barcoding strategy (Colston‐Nepali et al ., 2019) that enables the multiplexing of over 4500 GBS samples compatible with the highest throughput Illumina sequencing platforms (such as NovaSeq), thus enabling to tap into the economies of scale in sequencing (Figure 1g; HD‐GBS+).…”
Section: Figurementioning
confidence: 99%
“…With the availability of computational facilities and robust sequencing technologies, the importance of genomics for the identification of genes and pathways is undisputed. Notably, genome-wide scanning approaches and digital candidate gene identification approaches, such as QTL, LD mapping, GWAS, GBS, and functional annotation, either alone or in combination with traditional candidate gene approaches are now frequently used (Mackay and Powell, 2007;Götz et al, 2008;McCarthy et al, 2008;Chen et al, 2009;Zhang et al, 2010Zhang et al, , 2020Bush and Moore, 2012;Glaubitz et al, 2014;Torkamaneh et al, 2020). The following three subsections provide an overview of the strength of genomics, with special reference towards understanding endosperm variability (both across species and within the seed).…”
mentioning
confidence: 99%